Good Corporate Governance, Profitabilias, Financial Leverage dan Company Size : Income Smoothing - Dodi Suryadi (Jurnal Simki Economic, 2023)
The purpose of this study was to determine the effect of good corporate governance, profitability, financial leverage and company size on income smoothing. Sample from research. There are 60 companies in the manufacturing companies listed on the Indonesian stock exchange. The sampling technique used purposive sampling technique. Based on the analysis and discussion, the result is that good corporate governance partially has a significant effect on income smoothing with a significant value of 0.000. Profitability partially has a significant effect on income smoothing with a significant value of 0.000. Financial leverage partially has a significant effect on income smoothing with a significant value of 0.000. Partially company size has no significant effect on income smoothing with a significant value of 0.111. Good corporate governance, profitability, financial leverage and company size together have a significant effect on income smoothing with a significant value of 0.000.